Design and Development of Constructivist-Based Teaching Materials for Khat and Rasm to Improve Arabic Writing and Reading Skills: Desain dan Pengembangan Bahan Ajar Khat dan Rasm dengan Pendekatan Konstruktivisme untuk Meningkatkan Keterampilan Menulis dan Membaca Teks Arab - Siti Mutmainnah Panigoro; Ibnu Rawandhy N. Hula; Ratni Bt. Hj. Bahri; Hairuddin (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
This research focuses on the development of integrated teaching materials to enhance Arabic reading (mahārah qira'ah) and writing (mahārah kitābah) skills through a constructivist approach that incorporates calligraphic aesthetics (khat) and writing conventions (rasm) as supporting elements within Arabic language instruction. This integration does not position khat or rasm as separate subjects but embeds them pedagogically to strengthen students' understanding of Arabic script. The study is motivated by challenges in Arabic language learning, particularly the fragmentation between theory and practice and the lack of comprehensive teaching materials. The research method employs the Research and Development (R&D) model, utilizing the ADDIE approach, with 72 students and two teachers from MA Al-Huda Gorontalo. Experts in material, language, and media have validated the study. The results demonstrate high validation scores from experts (material expert: 92%, language expert: 88%, media expert: 78%), as well as proven effectiveness in field trials, with positive responses from students (79%) and teachers (88%). A significant improvement was observed in Arabic writing (+81%) and reading (+78%) skills, as measured through pretest–post-test analysis. The study concludes that the teaching materials developed—which integrate khat and rasm within a constructivist framework—effectively enhance Arabic literacy, supported by systematic material organization and flexible classroom application. Recommendations include further development of interactive features and broader trials across different educational levels. These findings contribute significantly to the advancement of innovative and effective Arabic teaching materials. Keywords: Arabic Calligraphy, Arabic Literacy, Constructivist Teaching Materials, Ottoman Rasm.